Implementasi Keamanan Jaringan Firewall Filtering Berbasis Mikrotik - Mutiarani Sinaga; Periman Lafau; Erna Simbolon; Santi Rosalinda Sihombing; David JM Sembiring (Institut Teknologi dan Bisnis Indonesia, 2025)
The development of network technology has shifted from cables to Wireless Local Area Networks (WLAN), allowing devices to connect and access the internet without cables, providing more flexibility. Internet use extends to various sectors, such as governments, companies and schools, making activities easier. However, unwise use of the internet can cause negative impacts, such as accessing irrelevant sites or logging into illegal servers, which compromise network security and performance, such as on Adam Net. To overcome this problem, it is necessary to implement Firewall Filtering using a Mikrotik router, which can control network traffic and limit access to certain sites, increasing network security on Adam Net